Genetic elements associated with antimicrobial resistance among avian pathogenic Escherichia coli. Issue 1 (December 2016) - Awad, Amal; Arafat, Nagah; Elhadidy, Mohamed
Abstract Background Avian-pathogenicEscherichia coli (APEC) are pathogenic strains ofE. coli that are responsible for one of the most predominant bacterial disease affecting poultry worldwide called avian colibacillosis. This study describes the genetic determinants implicated in antimicrobial resistance among APEC isolated from different broiler farms in Egypt. Methods A total of 116 APEC were investigated by serotyping, antimicrobial resistance patterns to 10 antimicrobials, and the genetic mechanisms underlying the antimicrobial-resistant phenotypes. Results Antibiogram results showed that the highest resistance was observed for ampicillin, tetracycline, nalidixic acid, and chloramphenicol. The detected carriage rate of integron was 29.3% (34/116). Further characterization of gene cassettes revealed the presence gene cassettes encoding resistance to trimethoprim (dfrA1, dfrA5, dfrA7, dfrA12 ), streptomycin/spectinomycin (aadA1, aadA2, aadA5, aadA23 ), and streptothricin (sat2 ). To our knowledge, this the first description of the presence ofaadA23 in APEC isolates. Analysis of other antimicrobial resistance types not associated with integrons revealed the predominance of resistance genes encoding resistance to tetracycline (tetA andtetB ), ampicillin (bla TEM ), chloramphenicol (cat1 ), kanamycin (aphA1 ), and sulphonamide (sul1 andsul2 ). Among ciprofloxacin-resistant isolates, the S83L mutation was the most frequently substitution observed in the quinolone resistance-determining region ofgyrA (56.3%). Thebla TEM andbla CTX−M−1 genes were the most prevalent among APEC isolates producing extended-spectrum beta-lactamase (ESβL). Conclusions These findings provided important clues about the role of integron-mediated resistance genes together with other independent resistance genes and chromosomal mutations in shaping the epidemiology of antimicrobial resistance inE. coli isolates from poultry farms in Egypt.